United Arab Emirates : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Arab Emirates. (IMF Staff Country Reports; Country Report, 2007)
The 2007 Article IV Consultation on the United Arab Emirates (UAE) examines the near- and medium-term outlook, inflation, and fiscal policy. The rapid expansion is supported by an outward-oriented development strategy and sustained high oil prices. Reforms are under way to strengthen the prudential and regulatory oversight of the banking system and the capital markets; to open the banking sector to greater competition; and to strengthen the legal framework for the financial sector. Executive Directors agreed that the key challenges will be to ensure sustained noninflationary growth and further diversification of the economy.